Nonlinear robust control applied to the six-phase induction machine - Ahmed, Yarba; Oumar, Aichetoune; Cherkaoui, Mohamed (Institute of Advanced Engineering and Science, 2024)
This paper proposes a nonlinear robust control for the six-phase induction machine (SPIM). It is based on the super twisting sliding mode (STSM) to ensure good decoupling and robust performance. This paper proposes also a comparative study between STSM and active disturbance rejection control (ADRC). We apply the rotor field-oriented control to ensure the decoupling between the magnitudes of the SPIM. Then we study the STSM control to regulate the rotor speed, the stator currents, and the rotor flux of the machine. The STSM ensures the same performance as the classical sliding mode control with the advantage of reducing the phenomenon of chattering. At the same time, the STSM command is compared to the ADRC command. The ADRC is one of the robust commands that makes it possible to estimate and eliminate internal or external disturbances. To test the robustness of the STSM and the ADRC, we implanted them in Simulink/MATLAB and the simulation results show the effectiveness of the STSM control compared to the ADRC control.